Prediction of Maternal and Fetal Syndrome of Preeclampsia - Sharma, Nidhi (IntechOpen, 2019)
The clinical syndrome of preeclampsia is due to vasospasm, endothelial dysfunction, and altered red cell zeta potential. It is a culmination of multiple etiologies and pathophysiologies modified by epigenetics and the human immune system. Since the etiology and pathogenesis of preeclampsia are segregated and multifactorial, there is no single clinical, biophysical, or biochemical marker that can predict all types of this condition. This book provides a set of tentative specific prediction markers that can be used to identify different subtypes of preeclampsia, classify pathogenesis, categorize treatment, and identify early signs of complications.